E-Commerce Barriers For SMEs In Select Asian Countries - Jalaeefar, Hoda (2009)
The present research intends to study the barriers which SMEs should overcome with in dealing with e-commerce particularly those barriers which emerged after the adoption of e-commerce and developing a website.